Effect of Material Type and Minimum Diameter of Specimens on the Fatigue Life - Syamsul Hadi; Anggit Murdani; Sudarmadji; Andhika Erlangga Setiawan Putra; Bambang Irawan; Hangga Wicaksono; Sza Sya Monica Valeria; Nila Alia (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2021)
The obstacle faced during the fatigue test is the waiting time which is quite long and inefficient, especially for test specimens made of ductile metal with waiting times of up to several days. The research method includes reducing the specimen radius to obtain a flexural stress approaching 400 MPa which was originally 229 MPa from a radius of 254 mm to 240 mm with the results of turning the original specimen obtained a minimum diameter of 8.6 mm is reduced to 7.3 mm at a maximum loading of 10 kg. Results of the research are brass specimens C3604BD type with a minimum diameter of 8.6 mm at a flexural stress of 298 MPa showing a fatigue life of 2455546 cycles with a test duration of 1754 minutes and a minimum specimen diameter of 7.3 mm at a flexural stress of 299 MPa showing a fatigue life of 684311 cycles with a test duration of 489 minutes which means that with a minimum specimen diameter of 7.3 mm the fatigue life is 3.59 times shorter than a minimum specimen diameter of 8.6 mm. Meanwhile, for aluminium AA1101 type with a minimum specimen diameter of 7.3 mm at a flexural stress of 182 MPa, the fatigue life is 422117 cycles with a test duration of 278 minutes and with a minimum specimen diameter of 8.6 mm at a flexural stress of 183 MPa, the fatigue life is 389232 cycles with a test duration of 302 minutes which means that with a minimum specimen diameter of 7.3 mm the fatigue life is 1.05 times shorter than the minimum specimen diameter of 8.6 mm or almost the same.